Formulation and Evaluation of Gel Mask Peel Off Moringa Leaf Extract (Moringa oleifera Lam) - Santi Agustina; Anna L Yusuf; Davit Nugraha (Ad-Dawaa : Journal of Pharmacy, 2023)
Peel-off gel mask is a practical mask, after drying the mask can be directly removed or removed without causing pain. This mask can also restore freshness and softness of the skin, even with regular use it can reduce fine wrinkles on facial skin. Moringa plants contain antioxidants, especially the leaves that contain flavonoids, causing Moringa leaves to be used as a source of natural antioxidants. The research method used is an experimental method with peel off gel mask preparation samples of Moringa leaf extract with various concentrations of 0% (F0), 5%(F1), 10%(F2), and15% (F3). Data analysis using One Way Anova test with 95% confidence level of significance = 0.05. Evaluation of the peel off gel mask preparation includes organoleptic test, homogeneity test, pH test, viscosity test, dispersibility test, adhesion test, dry time test and syneresis test. The results of the research F0, F1, F2 and F3 met the standard of the tests carried out such as organoleptic tests, pH tests, dispersibility tests, adhesion tests, dry time tests, and syneresis tests. The results of the One Way Anova statistical test for the pH test obtained a P-Value value of 0.63> 0.05, the dispersion test obtained a P-Value value of 0.02 0.05, the drying time test obtained a P-Value value of 0.00 (0.05) while the test dispersion and syneresis test there is an effect of giving concentration variations with a significance value of P < (0.05).